The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cells10102716
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines against COVID-19: Priority to mRNA-Based Formulations

Abstract: As of September 2021, twenty-one anti-COVID-19 vaccines have been approved in the world. Their utilization will expedite an end to the current pandemic. Besides the usual vaccine formats that include inactivated viruses (eight approved vaccines) and protein-based vaccines (four approved vaccines), three new formats have been validated: recombinant adenovirus (six approved vaccines), DNA (one approved vaccine), and messenger RNA (mRNA, two approved vaccines). The latter was the fastest (authorized in 2020 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…As a result of an unprecedented worldwide scientific effort, several vaccines against SARS‐CoV‐2 have been developed, relying on the concepts of mRNA‐ or adenovirus vector‐based vaccination, with reported success rates of approximately 90% in phase 3 pivotal trials [ 6 ]. A number of studies have shown that immune response to SARS‐CoV‐2 vaccination is adequate under most DMTs, but consistently found impaired response in pwMS receiving anti‐CD20 and sphingosine‐1‐phosphate receptor modulators (S1PM), although mostly focusing on humoral response [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of an unprecedented worldwide scientific effort, several vaccines against SARS‐CoV‐2 have been developed, relying on the concepts of mRNA‐ or adenovirus vector‐based vaccination, with reported success rates of approximately 90% in phase 3 pivotal trials [ 6 ]. A number of studies have shown that immune response to SARS‐CoV‐2 vaccination is adequate under most DMTs, but consistently found impaired response in pwMS receiving anti‐CD20 and sphingosine‐1‐phosphate receptor modulators (S1PM), although mostly focusing on humoral response [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moderna and Pfizer vaccines using a mutated sequence of the receptor-binding domain (RDB) that contains two consecutive prolines, lysine 986, and valine 987 ( 6 ) have been associated with high protection rates ( 7 ). Accumulating evidence demonstrates that the two doses of the BNT162b vaccine elicit either high IgG or neutralizing antibody responses ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, according to the World Health Organization (WHO), there are currently 73 COVID-19 vaccines that have entered clinical research, and more than 180 remain in preclinical research. The main types include nucleic acid, inactivated, live-attenuated, replicating viral vector vaccines, and virus-like particles vaccines [ 12 ]. Nucleic acid vaccines comprise mRNA and DNA vaccines, which are characterized by simple preparation, safe application, and high efficiency.…”
Section: Introductionmentioning
confidence: 99%